Concentration effect of aqueous synthesis on biphasic hydroxyapatite - β-tricalcium phosphate composition - Alqap, Asep Sofwan F.; Sopyan, Iis; Zubir, S. A. (Trans Tech Publications, Switzerland, 2010)
Hydroxyapatite of calcium phosphate materials, one of the most frequently used ceramic material in biomedical application, has been produced via chemical reaction involves both calcium and phosphorus precursors. Effect of suspension concentration on available phases was investigated using a basis of 2 mole % excess of calcium oxide. The synthesis was performed at 90°C until paste was obtained. To improve crystallinity, hydroxyapatite was calcined at 900°C. However, β-TCP appeared as trace which varied in fraction with suspension concentration. Varying concentration is then one approaching method in designing phase composition through which a functional material could be attained.